Risk factors, prevalence, and co-Morbidities of Hypertension in adult villagers in Kampung Tajau Laut, Kudat, Sabah, Malaysia - Fairrul Kadir; Mohammad Saffree Jeffree; Yusof Ibrahim; Tin, Tin Aye; Syed Shajee Husain; Fredie Robinson; Swe; Anna Antonia Asik; Choo, Wei Kei; Elsaharahap Hasan Basri; Liew, Kar Yan; Navin Ravi; et al. (2019)
Introduction: Hypertension is a condition where there is persistently raised pressure in the blood vessels. In Malay-sia, higher prevalence of hypertension could be explained by lifestyle factors such as higher rates of obesity, excess dietary intake of sodium and fat and lack of physical activity. The main objective of this study was to determine the prevalence, risk factors and co-morbidities of hypertension in villagers aged 18 years and above in Kampung Tajau Laut, Kudat, Sabah. Methods: Non-probability convenience sampling method was used to select a total of 210 villagers for interview, anthropometric examinations and blood pressure measurements. House to house and face to face interview by trained year four medical students done using a pretested validated questionnaire. The ques-tionnaire contained data on socioeconomic status, tobacco use, physical activity, diet, extra-salt use, family history of hypertension, co-morbidity, anthropometric measurements and blood pressure. Results: Respondents noted to be hypertensive were 67.6%, and out of this, 61.3% were undiagnosed. There was a significant association between hypertension and family history (Chi-squared test=38.280, p=0.000), hypertension and smoking status (Chi-squared test=7.673, p= 0.006), hypertension and obesity (Chi-squared test= 8.731, p=0.003), hypertension and gender (Chi-squared test=5.126, p=0.024), hypertension and age (Chi-squared test=26.110, p=0.000) of respondents. There was no significant association between hypertension with vegetable intake, fruit intake, physical activity, marital status, ethnicity, economic status, level of education, and occupational status of respondents. Half of the known hyperten-sive respondents have comorbidities with most commonly being dyslipidaemia and diabetes mellitus. Conclusion: Hypertension was found to have a significant association with family history, smoking status, obesity, age and gender among the studied population.